A homogenizing process of a high-nickel positive electrode of a lithium ion battery and a positive electrode slurry

CN122930832APending Publication Date: 2026-10-16JIANGSU HIGHSTAR BATTERY MFG CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611426612.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

1、导电剂分散困难:高镍材料本征电子电导率低(10-3-10-4S/cm),需添加≥3%的导电剂;单壁碳纳米管长径比大、易缠绕团聚,传统工艺中直接加入主材易导致碳管分散不均、过度剪切断裂而丧失长程导电能力;同时,导电炭黑与碳纳米管缺乏有序分散步骤,难以在颗粒表面形成均匀完整的点-线-面三维导电网络,导致极片面电阻偏高

Benefits of technology

1、本发明通过分批次等量投料高镍三元正极材料并配合慢搅刮壁与高速分散的节奏切换,使每批次粉体在导电胶液中均获得充分润湿空间和剪切传递效率,从源头避免局部过载导致的干粉团聚和颗粒破碎;全程将浆料温度严格控制在25-35℃,抑制高镍材料表面残碱与聚偏氟乙烯含氟基团之间的脱氟化氢副反应,防止浆料凝胶化和粘度失控。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930832A_ABST
    Figure CN122930832A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of lithium ion batteries, and discloses a homogenizing process of a high-nickel positive electrode of a lithium ion battery and a positive electrode slurry, which comprises the following steps: N-methyl pyrrolidone is mixed and stirred with polyvinylidene fluoride to form a uniform glue solution, and conductive carbon black is added; the first mixed solution is prepared by adopting first rotating speed and second rotating speed for step-by-step stirring; oil-based single-walled carbon nanotube conductive slurry is added into the first mixed solution and stirred and dispersed to obtain a conductive glue solution; high-nickel ternary positive electrode materials are added in batches; after each batch of high-nickel ternary positive electrode materials is added, the materials are first stirred at third rotating speed and scraped, and then dispersed at fourth rotating speed; after all the high-nickel ternary positive electrode materials are added, the dispersion treatment is continuously carried out to obtain a dispersion slurry; the viscosity of the dispersion slurry is adjusted, the dispersion slurry is deaerated in a vacuum environment, the deaerated slurry is screened and filtered, and the slurry is sealed and stored to obtain a lithium ion battery high-nickel positive electrode slurry. The application reduces particle agglomeration and improves the long-term stability of the slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and more specifically, to a homogenization process and cathode slurry for a high-nickel cathode of a lithium-ion battery. Background Technology

[0002] With the rapid development of new energy vehicles and the energy storage industry, lithium-ion batteries, as core energy storage devices, have become a focus of industry attention due to their energy density, cycle life, and safety. Cathode materials are the key components determining the energy density of lithium-ion batteries, among which high-nickel ternary cathode materials (such as LiNi) are particularly important. x Co y Mn2O2 (x≥0.6, typically represented by NCM811, NCM9 series, NCA, etc.) has become the mainstream choice for high-energy-density power batteries due to its high specific capacity and relatively low cost. However, with the increase of nickel content, high-nickel cathode materials have revealed many technical problems in the slurry preparation process, which seriously restricts their industrial application.

[0003] High-nickel materials commonly encounter the following problems during the slurry mixing process: 1. Difficulty in dispersing conductive agents: High-nickel materials have low intrinsic electronic conductivity (10). -3 -10 -4 (S / cm), ≥3% conductive agent needs to be added; single-walled carbon nanotubes have a large aspect ratio and are easy to entangle and agglomerate. In traditional processes, directly adding the main material can easily lead to uneven dispersion of carbon nanotubes, excessive shearing and breakage, and loss of long-range conductivity; at the same time, conductive carbon black and carbon nanotubes lack an orderly dispersion step, making it difficult to form a uniform and complete point-line-surface three-dimensional conductive network on the particle surface, resulting in high electrode surface resistance.

[0004] 2. Poor slurry stability: The surface of high-nickel materials is highly alkaline (pH≈11-12), and during the slurry mixing process, it is easy to undergo defluorination hydrogen side reaction with the fluorine-containing groups in polyvinylidene fluoride, resulting in slurry gelation and viscosity loss. Traditional slurry mixing process uses a large amount of material to be added at one time, and the local overload of powder leads to uneven wetting, which aggravates dry powder agglomeration and particle breakage, causing the slurry to settle, rebound viscosity, or even severely gel during storage or coating.

[0005] 3. Defects in coated electrode sheets: Microbubbles and agglomerates remaining in the slurry can cause pinholes, scratches and particle bumps on the electrode sheet surface during coating. In severe cases, this can lead to roller breakage or micro-short circuits in the battery. At the same time, improper control of slurry viscosity and solid content can easily cause fluctuations in coating surface density, affecting the battery's cycle performance and safety performance.

[0006] No effective solutions have yet been proposed to address the problems in the relevant technologies. Summary of the Invention

[0007] To address the problems in related technologies, this invention proposes a homogenization process and cathode slurry for high-nickel lithium-ion batteries, thereby overcoming the aforementioned technical problems in existing related technologies.

[0008] Therefore, the specific technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a slurry homogenization process for a high-nickel cathode of a lithium-ion battery, the process comprising the following steps: S1. Mix N-methylpyrrolidone with polyvinylidene fluoride and stir to form a uniform adhesive solution; S2. Add conductive carbon black to the uniform adhesive solution, and stir in stages using the first speed and the second speed to make the conductive carbon black uniformly dispersed to form dot-shaped conductive base, so as to prepare the first mixture. S3. Add oil-based single-walled carbon nanotube conductive slurry to the first mixture and stir to disperse. Use the dispersed conductive carbon black to achieve linear exfoliation of oil-based single-walled carbon nanotubes and form a point-line synergistic conductive framework with the point conductive base to obtain conductive adhesive. S4. Add high-nickel ternary cathode material to the conductive adhesive in batches. After each batch of high-nickel ternary cathode material is added, stir and scrape the wall at the third speed, and then disperse at the fourth speed. After all the high-nickel ternary cathode material is added, continue the dispersion process so that the conductive carbon black and single-walled carbon nanotubes form a three-dimensional conductive structure with entanglement, coating and network filling on the surface of the high-nickel ternary cathode material to obtain a dispersion slurry. S5. Add N-methylpyrrolidone to the dispersion slurry to adjust the slurry viscosity, and place it in a vacuum environment to degas, thereby obtaining a degassed slurry; S6. Filter the defoamed slurry through a sieve, seal and store it to obtain a high-nickel cathode slurry for lithium-ion batteries.

[0009] Secondly, the present invention provides a high-nickel cathode slurry for lithium-ion batteries, which is prepared by a homogenization process of the high-nickel cathode of the lithium-ion battery.

[0010] The beneficial effects of this invention are as follows: 1. This invention uses equal amounts of high-nickel ternary cathode material added in batches, combined with a rhythm of slow stirring and wall scraping and high-speed dispersion, to ensure that each batch of powder obtains sufficient wetting space and shear transfer efficiency in the conductive adhesive, thus avoiding dry powder agglomeration and particle breakage caused by local overload from the source; the slurry temperature is strictly controlled at 25-35℃ throughout the process to suppress the defluorination side reaction between residual alkali on the surface of high-nickel material and fluorinated groups of polyvinylidene fluoride, and to prevent slurry gelation and viscosity runaway.

[0011] 2. This invention pre-constructs a uniform and expansive point-line synergistic conductive framework by first wetting the conductive carbon black at low speed and then shearing it at high speed before adding the main material, and by pre-dilution the oil-based single-walled carbon nanotube conductive slurry before slowly adding and dispersing it at high speed. This allows the conductive agent to be quickly adsorbed and wrapped around the particle surface after the main material is added, which greatly shortens the dispersion time and improves the coating uniformity. At the same time, it avoids the carbon nanotubes from losing their long-range conductivity due to excessive shearing and breakage.

[0012] 3. This invention provides a suitable viscosity window by controlling the solid content of polyvinylidene fluoride / N-methylpyrrolidone adhesive to 6%-15% to balance wetting ability and flowability. After dispersion, N-methylpyrrolidone is added in small amounts multiple times to precisely adjust the solid content of the finished slurry to 65%-68%. Combined with high vacuum degassing to remove microbubbles and control solvent evaporation loss, this invention eliminates coating pinhole defects and uneven electrode surface density caused by bubble residue.

[0013] 4. This invention uses a double-layer superimposed screen to filter and intercept residual agglomerates and foreign matter. After filtration, it is immediately sealed and stored to isolate moisture and oxygen. Before coating, it is subjected to low-speed re-homogenization and 24-hour static stability verification to ensure that the slurry is restored to a uniform dispersion state before being loaded into the machine without stratification, skinning, or viscosity rebound. Ultimately, the resulting high-nickel positive electrode slurry for lithium-ion batteries has a fineness of ≤10μm, a coating surface density deviation of ≤±1.5%, and no scratches or bumps on the electrode surface. The three-dimensional conductive network is complete and stable, and the battery cycle performance is significantly improved. Attached Figure Description

[0014] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0015] Figure 1 This is a flowchart of a slurry mixing process for a high-nickel positive electrode of a lithium-ion battery according to an embodiment of the present invention; Figure 2 This is a flow state diagram of the slurry in Example 1 after 24 hours in the homogenization process of a high-nickel positive electrode for a lithium-ion battery according to an embodiment of the present invention. Figure 3 This is a surface state diagram of the slurry electrode sheet after rolling in Example 1 of the homogenization process of a high-nickel positive electrode for a lithium-ion battery according to an embodiment of the present invention. Detailed Implementation

[0016] To further illustrate the various embodiments, the present invention provides accompanying drawings, which are part of the disclosure of the present invention. These drawings are mainly used to illustrate the embodiments and can be used in conjunction with the relevant descriptions in the specification to explain the operating principles of the embodiments. With reference to these drawings, those skilled in the art should be able to understand other possible implementation methods and the advantages of the present invention. The components in the drawings are not drawn to scale, and similar component symbols are generally used to represent similar components.

[0017] According to an embodiment of the present invention, a homogenization process and cathode slurry for a high-nickel cathode of a lithium-ion battery are provided.

[0018] The present invention will now be further described in conjunction with the accompanying drawings and specific embodiments, such as... Figure 1 As shown, the slurry preparation process for a high-nickel positive electrode of a lithium-ion battery according to an embodiment of the present invention includes the following steps: S1. Mix and stir N-methylpyrrolidone (NMP) and polyvinylidene fluoride (PVDF) to form a uniform adhesive solution; In this optional embodiment, the step of mixing and stirring N-methylpyrrolidone and polyvinylidene fluoride to form a homogeneous adhesive includes: The N-methylpyrrolidone and polyvinylidene fluoride are continuously stirred for 3-4 hours at an orbital speed of 25-35 rpm and a rotational speed of 1500-2000 rpm to fully swell and dissolve, thereby obtaining a uniform adhesive solution; the solid content of the uniform adhesive solution is 6%-15%.

[0019] Specifically, the mass fraction of the polyvinylidene fluoride (PVDF) adhesive solution is 6%-12%. After stirring, the solution is allowed to stand for 1-2 hours to remove bubbles. Samples are taken to confirm that the adhesive solution is clear and transparent, without any undissolved particles visible to the naked eye, and has a viscosity of 8000-15000 mPa·s before it can be used for the next step.

[0020] S2. Add conductive carbon black (Li-435) to the uniform adhesive solution, and stir in stages using the first speed and the second speed to make the conductive carbon black uniformly dispersed to form dot-shaped conductive base, so as to prepare the first mixture. In this optional embodiment, the step of adding conductive carbon black to the homogeneous adhesive solution and then stirring in stages using a first speed and a second speed to uniformly disperse the conductive carbon black into dot-like conductive bases, in order to prepare the first mixture, includes: First, add the conductive carbon black to the uniform adhesive solution and stir and wet it at the first speed for 5-10 minutes. The first speed includes a revolution speed of 40-50 rpm and a rotation speed of 800-1000 rpm. Then disperse and stir at the second rotation speed for 60-90 minutes. The second rotation speed is a rotation speed of 3000-4000 rpm. During the stirring process, scrape the wall once every 15-20 minutes to prepare the first mixture. The fineness of the first mixture is ≤15μm.

[0021] Specifically, the amount of conductive carbon black (Li-435) added is 1.2%-2.0% of the active material mass; the specific surface area of ​​the conductive carbon black is 50-70 m² / g, and the particle size is 30-50 nm. A dispersion method of low-speed wetting followed by high-speed shearing is adopted. In the low-speed stage, the carbon black particles are fully wetted by the adhesive solution, and surface-adsorbed gases are expelled, avoiding excessive bubble generation in the high-speed stage. In the high-speed stage, strong shearing force breaks down the carbon black agglomerates, allowing them to be uniformly dispersed in the adhesive solution system. The system is scraped every 15-20 minutes to remove undispersed material adhering to the vessel wall and stirring paddle back into the system, ensuring uniform dispersion. A fineness control standard of ≤15 μm ensures that the carbon black agglomerates have been fully dissociated, providing a uniform point-like conductive basis for the subsequent point-anchoring dispersion of carbon nanotubes.

[0022] S3. Add oil-based single-walled carbon nanotube conductive slurry (CNT) to the first mixture and stir to disperse. Use the dispersed conductive carbon black to achieve linear exfoliation of oil-based single-walled carbon nanotubes and form a point-line synergistic conductive framework with the point conductive base to obtain conductive adhesive. In this optional embodiment, the addition of oil-based single-walled carbon nanotube conductive slurry to the first mixture and its stirring and dispersion, along with the dispersed conductive carbon black, enables the linear exfoliation of the oil-based single-walled carbon nanotubes, forming a point-line synergistic conductive framework with the dotted conductive base, to obtain a conductive adhesive comprising: N-methylpyrrolidone was used to pre-dilute the oil-based single-walled carbon nanotube conductive slurry. After dilution, the solid content of the oil-based single-walled carbon nanotube conductive slurry decreased from 0.4% to below 0.2%, and then it was slowly added to the first mixture. After addition, stir at a rotation speed of 3000-4000 rpm. When the slurry is uniformly black and there are no visible carbon nanotube agglomerates, take a sample to obtain the conductive adhesive.

[0023] Specifically, oil-based single-walled carbon nanotube conductive slurry is pre-diluted with N-methylpyrrolidone at a mass ratio of 1:1 to 1:1.5 to reduce the solid content of the carbon nanotube conductive slurry to 0.16%-0.2%. After pre-dilution, it is slowly added to the first mixture over a time of 3-5 minutes.

[0024] The amount of oil-based single-walled carbon nanotube conductive slurry added is calculated based on the dry weight of carbon nanotubes, and is 0.1%-0.5% of the active material mass. The oil-based single-walled carbon nanotubes are further dispersed in the already dispersed carbon black colloid system. The pre-dilution step reduces the viscosity of the carbon nanotube slurry, allowing the carbon nanotube bundles to initially expand before entering the system, reducing the time required for high-speed untangling; slow addition avoids excessively high local carbon nanotube concentrations leading to re-agglomeration; carbon black particles act as anchors, promoting linear exfoliation of carbon nanotubes and maintaining dispersion stability. After the conductive material is pre-dispersed and mixed, when the main material (i.e., high-nickel ternary cathode material) is subsequently added, the single-walled carbon nanotubes wrap around and coat the surface of the main material, the conductive carbon black fills the gaps in the network, and the single-walled carbon nanotubes undergo secondary bridging, constructing a three-dimensional conductive network structure.

[0025] The carbon nanotubes are single-walled carbon nanotubes with a diameter of 1-5 nm and a length of 5-20 μm. The solid content of the single-walled carbon nanotube conductive slurry is 0.4%. After sampling and dilution, the carbon nanotube dispersion system is tested with a laser particle size analyzer to determine the dispersion endpoint if the D90 is ≤20 μm.

[0026] S4. Add high-nickel ternary cathode material to the conductive adhesive in batches. After each batch of high-nickel ternary cathode material is added, stir and scrape the wall at the third speed, and then disperse at the fourth speed. After all the high-nickel ternary cathode material is added, continue the dispersion process so that the conductive carbon black and single-walled carbon nanotubes form a three-dimensional conductive structure with entanglement, coating and network filling on the surface of the high-nickel ternary cathode material to obtain a dispersion slurry. In this optional embodiment, the step of adding high-nickel ternary cathode material to the conductive adhesive in batches includes: All high-nickel ternary cathode materials are divided into two equal parts and fed in batches, with the mass of each batch accounting for 50% of the total mass of all high-nickel ternary cathode materials; the mass fraction of nickel in the high-nickel ternary cathode materials is ≥90%.

[0027] In this optional embodiment, after each batch of high-nickel ternary cathode material is fed, it is first stirred and scraped at a third rotation speed, and then dispersed at a fourth rotation speed; after all the high-nickel ternary cathode material has been fed, the dispersion process continues, so that conductive carbon black and single-walled carbon nanotubes form a three-dimensional conductive structure with entanglement, coating and network filling on the surface of the high-nickel ternary cathode material, so as to obtain a dispersion slurry comprising: After each batch of material is fed, it is stirred at the third rotation speed for 5-10 minutes and the wall is scraped to fully wet the powder. The third rotation speed includes a revolution speed of 40-50 rpm and a rotation speed of 800-1000 rpm. Then disperse for 10-15 minutes at the fourth rotation speed, which includes a revolution speed of 40-50 rpm and a rotation speed of 3000-4000 rpm; After all materials have been added, disperse at the fourth rotation speed for 150-200 minutes, with the dispersion temperature controlled at 25-35℃, to obtain a dispersion slurry with a fineness ≤10μm.

[0028] Specifically, the high-nickel ternary cathode material has a nickel content ≥90%, a D50 of 8-15μm, and a specific surface area of ​​0.8-1.1m² / g. Feeding in two equal portions avoids localized powder overload caused by large-scale single feeding, ensuring each batch of powder receives sufficient wetting space and shear transfer efficiency. Slow stirring combined with wall scraping ensures thorough mixing and wetting of the powder with the conductive adhesive. High-speed dispersion allows the pre-dispersed conductive agent to rapidly adsorb and entangle on the surface of the cathode material particles, while conductive carbon black fills the gaps between particles and in the carbon nanotube network. Single-walled carbon nanotubes bridge the gaps between particles, forming a three-dimensional, full-order conductive network of points, lines, and surfaces. Temperature is strictly controlled at 25-35℃ to suppress the defluorination side reaction between residual alkali on the high-nickel material surface and the fluorinated groups of PVDF, preventing slurry gelation and viscosity runaway. A fineness standard of ≤10μm ensures uniform dispersion of the main particles and no residual agglomeration.

[0029] S5. Add N-methylpyrrolidone to the dispersion slurry to adjust the slurry viscosity, and place it in a vacuum environment to degas, thereby obtaining a degassed slurry; In this optional embodiment, the step of adding N-methylpyrrolidone to the dispersion slurry to adjust the slurry viscosity and then placing it under vacuum to degas and obtain a degassed slurry includes: N-methylpyrrolidone was added in stages to adjust the viscosity of the slurry. After adjustment, the solid content of the finished slurry was controlled at 65%-68%. Deaeration was carried out for 30-120 minutes under vacuum conditions of -85 kPa and revolution speed of 10-30 rpm. After deaeration, the pressure was restored to normal and it was confirmed that there were no visible bubbles on the surface of the slurry to obtain deaerated slurry.

[0030] Specifically, adding NMP in small amounts multiple times allows for precise viscosity control to 5000-8000 mPa·s, avoiding sudden drops in viscosity and solid content deviations caused by adding a large amount at once. The solid content of the finished slurry is controlled at 65%-68%, balancing leveling and drying efficiency during coating. During the high-vacuum degassing stage, the rotation speed is set to 10-30 rpm, continuously agitating the slurry to encourage internal bubbles to rise and escape. The -85 kPa high-vacuum environment effectively removes microbubbles and residual moisture entrained in the slurry, while reducing NMP solvent evaporation loss and maintaining stable slurry solid content. After degassing, atmospheric pressure is restored, and it is confirmed that there are no visible bubbles on the slurry surface, ensuring that pinhole defects on the electrode sheet will not occur due to bubble rupture during coating.

[0031] S6. Filter the defoamed slurry through a sieve, seal and store it to obtain a high-nickel cathode slurry for lithium-ion batteries.

[0032] In this optional embodiment, the step of filtering the defoamed slurry through a sieve and sealing it for storage to obtain a high-nickel cathode slurry for lithium-ion batteries includes: The defoamed slurry was filtered using a double-layered 100-150 mesh screen, and then immediately sealed and stored to obtain a high-nickel cathode slurry for lithium-ion batteries. Before coating, the high-nickel positive electrode slurry of lithium-ion battery was stirred at 10-20 rpm for 10 min to re-homogenize it. A sample was then taken and allowed to stand for 24 h to verify that there was no layering, no skinning, and the viscosity rebound rate was ≤15%. After the sample was deemed qualified, the coating was carried out.

[0033] In this optional embodiment, the mass ratio of polyvinylidene fluoride, conductive carbon black, oil-based single-walled carbon nanotubes, and high-nickel ternary cathode material is 1.0-3.0%: 1.0-3.0%: 0.1-0.5%: 95-98%; wherein the solid content of the oil-based single-walled carbon nanotube conductive slurry is 0.4%.

[0034] Specifically, using a 100-150 mesh double-layer superimposed sieve effectively intercepts residual trace agglomerates and foreign matter that may be mixed in from the outside, ensuring the cleanliness of the slurry. After filtration, it is immediately sealed and stored to isolate it from environmental moisture and oxygen, preventing moisture absorption and deterioration of the high-nickel material surface and hygroscopic degradation of PVDF. Before coating, it is re-homogenized at a low speed of 10-20 rpm for 10 minutes to restore the slurry to a uniform dispersion state, preventing fluctuations in coating surface density due to differences in solid content between the upper and lower layers during processing. Samples are allowed to stand for 24 hours to verify no stratification, no skinning, and a viscosity rebound rate ≤15%, serving as the final criterion for judging the stability of the slurry before coating, ensuring good processing consistency throughout the coating cycle. The resulting high-nickel cathode slurry for lithium-ion batteries exhibits a coating surface density deviation ≤±1.5%, with no scratches or bumps on the electrode surface, and a complete and stable three-dimensional conductive network.

[0035] Example 1 A high-nickel cathode slurry for lithium-ion batteries includes a cathode material, a conductive agent, and a binder. The mass ratio of polyvinylidene fluoride, conductive carbon black, oil-based single-walled carbon nanotubes, and high-nickel ternary cathode material is 1.2%:1.8%:0.2%:96.8%. The solid content of the oil-based single-walled carbon nanotube conductive slurry is 0.4%.

[0036] The homogenization process for the above-mentioned high-nickel cathode slurry for lithium-ion batteries includes the following steps: S1. Add N-methylpyrrolidone and polyvinylidene fluoride to a double planetary mixer and stir continuously for 3.5 hours at a revolution speed of 30 rpm and a rotation speed of 1800 rpm to fully swell and dissolve the polyvinylidene fluoride, and obtain a uniform adhesive solution with a solid content of 8%. S2. Add conductive carbon black (Li-435) to the uniform adhesive solution. First, stir and wet the solution at a revolution speed of 45 rpm and a rotation speed of 800 rpm for 5 min. Then, disperse and stir at a rotation speed of 3500 rpm for 60 min. During the stirring process, scrape the wall once every 15 min to obtain the first mixture with a fineness of ≤15μm. S3. Take a small amount of N-methylpyrrolidone to pre-dilute the oil-based single-walled carbon nanotube conductive slurry. After dilution, the solid content is reduced to below 0.2%. Slowly add it to the first mixture. After adding, stir at a rotation speed of 3500 rpm for 60 minutes. Take a sample after the slurry is uniformly black and there are no visible carbon nanotube agglomerates. The conductive adhesive solution is then obtained. S4. Divide all the high-nickel ternary cathode material into two equal portions and add them to the conductive adhesive solution in batches. After the first batch is added, stir at a revolution speed of 45 rpm and a rotation speed of 800 rpm for 5 minutes and scrape the wall, then disperse at a high speed of 45 rpm and a rotation speed of 3500 rpm for 10 minutes. After the second batch is added, stir at a revolution speed of 45 rpm and a rotation speed of 800 rpm for 5 minutes and scrape the wall, then disperse at a high speed of 45 rpm and a rotation speed of 3500 rpm for 180 minutes. The dispersion process is controlled at a temperature of 25-35℃. The nickel content in the high-nickel ternary cathode material is ≥90% by mass. S5. N-methylpyrrolidone was added in small amounts and multiple times to adjust the viscosity of the slurry. After adjustment, the solid content of the finished slurry was 68%. The slurry was degassed for 60 minutes under vacuum of -85 kPa and revolution speed of 20 rpm. After degassed, the pressure was restored to normal and it was confirmed that there were no visible bubbles on the surface of the slurry. The degassed slurry was obtained. S6. The deaerated slurry was filtered using a 120-mesh double-layer superimposed sieve. After filtration, it was immediately sealed and stored to obtain a high-nickel cathode slurry for lithium-ion batteries. The slurry viscosity was 6306 mPa·s, the solid content was 68.0%, and the fineness was 10 μm. Before coating, it was stirred at 15 rpm for 10 min to re-homogenize. Samples were taken and allowed to stand for 24 h to verify that there was no stratification or skin formation. The viscosity rebound rate was 14.3%. After being deemed qualified, coating was carried out.

[0037] Example 2 A high-nickel cathode slurry for lithium-ion batteries includes a cathode material, a conductive agent, and a binder. The mass ratio of polyvinylidene fluoride, conductive carbon black, oil-based single-walled carbon nanotubes, and high-nickel ternary cathode material is 2.0%:1.5%:0.3%:96.2%. The solid content of the oil-based single-walled carbon nanotube conductive slurry is 0.4%.

[0038] The homogenization process for the above-mentioned high-nickel cathode slurry for lithium-ion batteries includes the following steps: S1. Add N-methylpyrrolidone and polyvinylidene fluoride to a double planetary mixer and stir continuously for 3.5 hours at a revolution speed of 30 rpm and a rotation speed of 1800 rpm to fully swell and dissolve the polyvinylidene fluoride, and obtain a uniform adhesive solution with a solid content of 10%. S2. Add conductive carbon black (Li-435) to the uniform adhesive solution. First, stir and wet the solution at a revolution speed of 40 rpm and a rotation speed of 800 rpm for 5 min. Then, disperse and stir at a rotation speed of 3500 rpm for 60 min. During the stirring process, scrape the wall once every 15 min to obtain the first mixture with a fineness ≤15μm. S3. Take a small amount of N-methylpyrrolidone to pre-dilute the oil-based single-walled carbon nanotube conductive slurry. After dilution, the solid content is reduced to below 0.2%. Slowly add it to the first mixture. After adding, stir at a rotation speed of 3500 rpm for 60 minutes. Take a sample after the slurry is uniformly black and there are no visible carbon nanotube agglomerates. The conductive adhesive solution is then obtained. S4. Divide all the high-nickel ternary cathode material into two equal portions and add them to the conductive adhesive solution in batches. After the first batch is added, stir at a revolution speed of 45 rpm and a rotation speed of 800 rpm for 5 minutes and scrape the wall, then disperse at a high speed of 45 rpm and a rotation speed of 4000 rpm for 10 minutes. After the second batch is added, stir at a revolution speed of 45 rpm and a rotation speed of 800 rpm for 5 minutes and scrape the wall, then disperse at a high speed of 45 rpm and a rotation speed of 4000 rpm for 180 minutes. The dispersion process is controlled at a temperature of 25-35℃. The nickel content in the high-nickel ternary cathode material is ≥90% by mass. S5. N-methylpyrrolidone was added in small amounts and multiple times to adjust the viscosity of the slurry. After adjustment, the solid content of the finished slurry was 67%. The slurry was degassed for 90 minutes under a vacuum of -85 kPa and a revolution speed of 20 rpm. After degassed, the pressure was restored to normal and it was confirmed that there were no visible bubbles on the surface of the slurry. The degassed slurry was obtained. S6. The deaerated slurry was filtered using a 120-mesh double-layer superimposed sieve. After filtration, it was immediately sealed and stored to obtain a high-nickel cathode slurry for lithium-ion batteries. The slurry viscosity was 6522 mPa·s, the solid content was 67.0%, and the fineness was 8 μm. Before coating, it was stirred at 15 rpm for 10 min to re-homogenize. Samples were taken and allowed to stand for 24 h to verify that there was no stratification or skin formation. The viscosity rebound rate was 4.9%. After being deemed qualified, coating was carried out.

[0039] Comparative Example 1 A lithium-ion battery positive electrode slurry includes a positive electrode material, a conductive agent, and a binder, with the same components and mass ratios as in Example 1.

[0040] The above-mentioned homogenization process for lithium-ion battery cathode slurry includes the following steps: S1. Add N-methylpyrrolidone and polyvinylidene fluoride to a double planetary mixer and stir continuously for 3.5 hours at a revolution speed of 30 rpm and a rotation speed of 1800 rpm to obtain a uniform adhesive solution. S2. Add conductive carbon black (Li-435) to the uniform adhesive solution. First, stir at a revolution speed of 45 rpm and a rotation speed of 800 rpm for 5 minutes, then stir at a high speed of 3500 rpm for 60 minutes. Scrape the wall once every 15 minutes to obtain the mixture. S3. Divide all the high-nickel ternary cathode material into two equal parts and add them to the mixture. After each batch is added, stir for 5 minutes at a revolution speed of 45 rpm and a rotation speed of 800 rpm, and scrape the wall. Then disperse at a rotation speed of 3500 rpm. After all the materials are added, disperse at a rotation speed of 3500 rpm for 60 minutes. The nickel content in the high-nickel ternary cathode material is ≥90% by mass. S4. Add oil-based single-walled carbon nanotube conductive slurry to the above slurry and stir at high speed of 3500 rpm for 180 min. S5. N-methylpyrrolidone was added to adjust the viscosity of the slurry, and degassing was performed under vacuum of -85 kPa and rotation speed of 20 rpm to obtain a degassed slurry. S6, after being filtered through a 120-mesh sieve, the output slurry viscosity is 5839 mPa·s and the fineness is 10 μm.

[0041] The difference between Comparative Example 1 and Example 1 is that the oil-based single-walled carbon nanotube conductive slurry is added after the main material, rather than premixed with conductive carbon black to form a conductive adhesive before the main material is added.

[0042] The stability of the high-nickel lithium-ion battery slurry in the above embodiments and comparative examples was tested, and the test results are shown in Table 1 below.

[0043] Table 1: Stability of high-nickel cathode slurry The sheet resistance of the high-nickel lithium-ion electrode sheets in the above embodiments and comparative examples was tested, and the test results are shown in Table 2 below.

[0044] Table 2: Sheet resistance of lithium-ion electrodes in high-nickel system Note: The surface resistance data in Table 2 are the test values ​​of two test points on the same electrode.

[0045] The test data from Examples 1, 2, and Comparative Example 1 show that Examples 1 and 2, using the homogenization process of this invention, achieve in-situ passivation by pre-dispersing conductive carbon black and single-walled carbon nanotubes in the conductive adhesive, adding high-nickel ternary cathode material in batches, and strictly controlling the dispersion temperature. This allows the conductive carbon black to preferentially adsorb onto the alkaline active sites on the cathode material surface, resulting in excellent slurry stability. The 24-hour viscosity rebound rate of Example 1 was 14.3%, and that of Example 2 was 4.9%, both ≤15%, with no layering, skinning, or gelation. In contrast, Comparative Example 1, using the traditional process of adding carbon nanotubes later, showed a 24-hour viscosity rebound rate of 466.5%, with severe gelation in the slurry, indicating poor performance.

[0046] Examples 1 and 2 ensured ideal dispersion of both conductive carbon black and single-walled carbon nanotubes by controlling the fineness of the intermediate (first mixture fineness ≤15μm) and the fineness of the finished product (dispersion slurry fineness ≤10μm) in a stepwise manner, achieving the orderly construction of a point-line-surface three-dimensional conductive network. Electrode surface resistivity tests showed that the surface resistivity at the two test points in Example 1 was 48.31mΩ and 53.41mΩ, in Example 2 it was 49.10mΩ and 55.47mΩ, while in Comparative Example 1 it was as high as 88.47mΩ and 91.02mΩ. The surface resistivity of the examples was reduced by more than 40% compared to the comparative example, indicating a significant improvement in conductivity. The smooth surface of the rolled electrode, free of particle protrusions, confirmed the integrity and effectiveness of the three-dimensional conductive structure.

[0047] According to a second embodiment of the present invention, a high-nickel cathode slurry for lithium-ion batteries is also provided, which is prepared by the homogenization process of the high-nickel cathode for lithium-ion batteries.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A slurry homogenization process for a high-nickel positive electrode of a lithium-ion battery, characterized in that, The process includes the following steps: S1. Mix N-methylpyrrolidone with polyvinylidene fluoride and stir to form a uniform adhesive solution; S2. Add conductive carbon black to the uniform adhesive solution, and stir in stages using the first speed and the second speed to make the conductive carbon black uniformly dispersed to form dot-shaped conductive base, so as to prepare the first mixture. S3. Add oil-based single-walled carbon nanotube conductive slurry to the first mixture and stir to disperse. Use the dispersed conductive carbon black to achieve linear exfoliation of oil-based single-walled carbon nanotubes and form a point-line synergistic conductive framework with the point conductive base to obtain conductive adhesive. S4. Add high-nickel ternary cathode material to the conductive adhesive in batches. After each batch of high-nickel ternary cathode material is added, stir and scrape the wall at the third speed, and then disperse at the fourth speed. After all the high-nickel ternary cathode material is added, continue the dispersion process so that the conductive carbon black and single-walled carbon nanotubes form a three-dimensional conductive structure with entanglement, coating and network filling on the surface of the high-nickel ternary cathode material to obtain a dispersion slurry. S5. Add N-methylpyrrolidone to the dispersion slurry to adjust the slurry viscosity, and place it in a vacuum environment to degas, thereby obtaining a degassed slurry; S6. Filter the defoamed slurry through a sieve, seal and store it to obtain a high-nickel cathode slurry for lithium-ion batteries.

2. The slurry preparation process for a high-nickel positive electrode of a lithium-ion battery according to claim 1, characterized in that, The mass ratio of polyvinylidene fluoride, conductive carbon black, oil-based single-walled carbon nanotubes, and high-nickel ternary cathode material is 1.0-3.0%: 1.0-3.0%: 0.1-0.5%: 95-98%; wherein the solid content of the oil-based single-walled carbon nanotube conductive slurry is 0.4%.

3. The homogenization process for a high-nickel positive electrode of a lithium-ion battery according to claim 1, characterized in that, The step of mixing and stirring N-methylpyrrolidone and polyvinylidene fluoride to form a uniform adhesive solution includes: The N-methylpyrrolidone and polyvinylidene fluoride are continuously stirred for 3-4 hours at an orbital speed of 25-35 rpm and a rotational speed of 1500-2000 rpm to fully swell and dissolve, thereby obtaining a uniform adhesive solution; the solid content of the uniform adhesive solution is 6%-15%.

4. The slurry homogenization process for a high-nickel positive electrode of a lithium-ion battery according to claim 1, characterized in that, The step of adding conductive carbon black to a uniform adhesive solution and then stirring in stages using a first speed and a second speed to uniformly disperse the conductive carbon black into dot-like conductive bases, in order to prepare the first mixture, includes: First, add the conductive carbon black to the uniform adhesive solution and stir and wet it at the first speed for 5-10 minutes. The first speed includes a revolution speed of 40-50 rpm and a rotation speed of 800-1000 rpm. Then disperse and stir at the second rotation speed for 60-90 minutes. The second rotation speed is a rotation speed of 3000-4000 rpm. During the stirring process, scrape the wall once every 15-20 minutes to prepare the first mixture. The fineness of the first mixture is ≤15μm.

5. The slurry homogenization process for a high-nickel positive electrode of a lithium-ion battery according to claim 1, characterized in that, The process involves adding an oil-based single-walled carbon nanotube conductive slurry to the first mixture and stirring to disperse it. The dispersed conductive carbon black is used to achieve linear exfoliation of the oil-based single-walled carbon nanotubes, forming a point-line synergistic conductive framework with the dotted conductive base, to obtain a conductive adhesive comprising: N-methylpyrrolidone was used to pre-dilute the oil-based single-walled carbon nanotube conductive slurry. After dilution, the solid content of the oil-based single-walled carbon nanotube conductive slurry decreased from 0.4% to below 0.2%, and then it was slowly added to the first mixture. After addition, stir at a rotation speed of 3000-4000 rpm. When the slurry is uniformly black and there are no visible carbon nanotube agglomerates, take a sample to obtain the conductive adhesive.

6. The slurry homogenization process for a high-nickel positive electrode of a lithium-ion battery according to claim 1, characterized in that, The step-by-step addition of high-nickel ternary cathode material to the conductive adhesive includes: All high-nickel ternary cathode materials are divided into two equal parts and fed in batches, with the mass of each batch accounting for 50% of the total mass of all high-nickel ternary cathode materials; the mass fraction of nickel in the high-nickel ternary cathode materials is ≥90%.

7. The slurry preparation process for a high-nickel positive electrode of a lithium-ion battery according to claim 6, characterized in that, After each batch of high-nickel ternary cathode material is fed, it is first stirred and scraped at a third rotation speed, and then dispersed at a fourth rotation speed. After all the high-nickel ternary cathode material has been fed, the dispersion process continues, so that conductive carbon black and single-walled carbon nanotubes form a three-dimensional conductive structure with entanglement, coating and network filling on the surface of the high-nickel ternary cathode material, so as to obtain a dispersion slurry comprising: After each batch of material is fed, it is stirred at the third rotation speed for 5-10 minutes and the wall is scraped to fully wet the powder. The third rotation speed includes a revolution speed of 40-50 rpm and a rotation speed of 800-1000 rpm. Then disperse for 10-15 minutes at the fourth rotation speed, which includes a revolution speed of 40-50 rpm and a rotation speed of 3000-4000 rpm; After all materials have been added, disperse at the fourth rotation speed for 150-200 minutes, with the dispersion temperature controlled at 25-35℃, to obtain a dispersion slurry with a fineness ≤10μm.

8. The slurry homogenization process for a high-nickel positive electrode of a lithium-ion battery according to claim 1, characterized in that, The step of adding N-methylpyrrolidone to the dispersion slurry to adjust the slurry viscosity and then placing it under vacuum to degas, thereby obtaining a degassed slurry, includes: N-methylpyrrolidone was added in stages to adjust the viscosity of the slurry. After adjustment, the solid content of the finished slurry was controlled at 65%-68%. Deaeration was carried out for 30-120 minutes under vacuum conditions of -85 kPa and revolution speed of 10-30 rpm. After deaeration, the pressure was restored to normal and it was confirmed that there were no visible bubbles on the surface of the slurry to obtain deaerated slurry.

9. The slurry homogenization process for a high-nickel positive electrode of a lithium-ion battery according to claim 1, characterized in that, The process of filtering the defoamed slurry through a sieve and sealing it for storage to obtain a high-nickel positive electrode slurry for lithium-ion batteries includes: The defoamed slurry was filtered using a double-layered 100-150 mesh screen, and then immediately sealed and stored to obtain a high-nickel cathode slurry for lithium-ion batteries. Before coating, the high-nickel cathode slurry for lithium-ion batteries was stirred at 10-20 rpm for 10 minutes to re-homogenize it. Samples were then taken and allowed to stand for 24 hours to verify that there was no layering, no skinning, and a viscosity rebound rate of ≤15%. After the sample was deemed qualified, coating was carried out.

10. A high-nickel cathode slurry for lithium-ion batteries, characterized in that: It is prepared by the homogenization process of the high-nickel positive electrode of lithium-ion battery as described in any one of claims 1-9.